The disengagement of visual attention in Alzheimer's disease: a longitudinal eye-tracking study - Crawford, Trevor J. (Frontiers in Aging Neuroscience, 2015)
Introduction: Eye tracking provides a convenient and promising biological marker of cognitive impairment in patients with neurodegenerative disease. Here we report a longitudinal study of saccadic eye movements in a sample of patients with Alzheimer's disease and elderly control participants who were assessed at the start of the study and followed up 12-months later. Methods: Eye movements were measured in the standard gap and overlap paradigms, to examine the longitudinal trends in the ability to disengage attention from a visual target. Results: Overall patients with Alzheimer's disease had slower reaction times than the control group. However, after 12-months, both groups showed faster and comparable reductions in reaction times to the gap, compared to the overlap stimulus. Interestingly, there was a general improvement for both groups with more accurately directed saccades and speeding of reaction times after 12-months. Conclusions: These findings point to the value of longer-term studies and follow-up assessment to ascertain the effects of dementia on oculomotor control.